Age structure and diameter distribution in a southern Swedish beech dominated landscape - Churski, Marcin (SLU/Southern Swedish Forest Research Centre, 2006)
Tree ages and tree diameters were investigated in an 800 ha south Swedish beech dominated landscape with old-growth associated conservational values. Ca. 1200 trees from 53 sites with beech present were used in the analysis. At landscape level, the tree diameter distribution revealed a rotated sigmoid pattern without logarithmic transformation, well in accordance with existing models of size structure and suggesting that the forest is under a small-scale disturbance regime. The age distribution at the landscape scale was irregular with prominent peaks and absent recruitment periods, suggesting occurrence of disturbances. The analysis of age over diameter showed that there was a low age-diameter correlation. Age distribution revealed existence of three cohorts that originated in the periods 1720-1760, 1850-1900 and 1930-1950 between which low recruitment of regeneration occurred. Forest utilisation is suggested to be a major reason for the irregular age structure and the different cohorts' history.